CAWriter : using an Activity System perspective to inform the design of tools to support early career Ph.D. candidates - Byrne, Jake Rowan (Trinity College (Dublin, Ireland). School of Computer Science & Statistics, 2014)
This thesis adheres to the view that the purpose of a Ph.D. is to both make a significant contribution to knowledge and to provide the candidate with the skills necessary to conduct "independent" research, culminating in a professional qualification. This work advocates the proposition that to make a significant contribution to knowledge will manifest from a “Knowledge Work” process and that the skills necessary are acquired through a process of environmental and sociological enculturation. The literature review develops the idea that writing, as a creative process, is synonymous with and a subset of this “Knowledge Work”. The literature review culminates in the development of an Activity System that creates a theoretical framework with which to describe the Ph.D. process and a set of design heuristics distilled from the literature which highlight elements to be considered when design for the Ph.D. process: pedagogical contexts, activities and skills. Within the Computer Science context within which this research is being conducted and participatory action research methodology, a computer program toolkit, CAWriter, was designed to support novice Ph.D. candidates with their early dissertation writing activities and act as a technology probe for this class of application. This toolkit was developed through an iterative Participatory Design process and was evaluated using a set of design heuristics developed based on the literature review. The system was evaluated by six single session users and four one to five month users. The findings indicate that the designed tools do in fact largely support the skills and activities as the four users demonstrated extensive use of a variety of the embedded tools. However there is still room for improvement and only early stage activities are supported, leaving room to expand the system to cater for more advanced activities such as collaboration, data analysis and revision. The central contributions of this work are an Activity System to describe the Ph.D. process, a set of design heuristics listing the necessary skills and activities to be supported by tools aimed at supporting Ph.D. candidates or novice researchers in general. Finally a tool, CAWriter, is presented and evaluated with real users in legitimate context, as an encapsulation of aforementioned design heuristics and Activity System perspective of the Ph.D. process.
Keywords: Computer Science, Ph.D.; Ph.D. Trinity College Dublin